Etiological Spectrum of Pancytopenia in Adults Based on Bone Marrow Examination in a Tertiary Care Hospital - Maryam Zulfiqar, Ayesha Sarwar, Bushra Anam Ali, Aqsa Liaqat, Tehseen Rafaqat, Sher Ali (Drugs and Cell Therapies in Hematology, 2021)
Objective:To determine various etiological causes of pancytopenia in patients by bone marrow biopsy Material and methods:Prospective study performed at the department of pathology, Pakistan institute of medical sciences for a period of 2 years. Total of bone marrow biopsies were performed, out of which 250 patients presented with pancytopenia on peripheral film. Out of 250 patients 115 patients were in pediatric age group and 135 patients were in adult age group. All the patients underwent bone marrow biopsy for diagnosis. Results:A total of 800 bone marrows were performed in two years from October 2017 to October 2019. Out of those 135patients presented with pancytopenia. Male to female ratio was 1.22:1. Most common conditions associated with pancytopenia were:megaloblastic anemia (29.6%) followed by infection related changes (26.6), aplasia (10.3%), reactive marrow (9.6%), acute leukemia’s (5.9%),chronic leukemia (3.7), iron deficiency anemia (3.7%), hypersplenism (2.9%), myelodysplastic syndrome (2.9%), multiple myeloma (2.2%), mixed deficiency anemia (1.4%), myelofibrosis. (0.74%). The most common presenting complaints were fever (54.8%), general body weakness with body aches (31.8%), pallor (31.1%), diarrhea and vomiting (25.9%), bleeding (14.8%) and on clinical examination there was hepatomegaly (12%) and splenomegaly (16.6%) noted. Conclusion:pancytopenia is a routine observation in our daily practice. To rule out the cause’s bone marrow biopsy should be choice of investigation in such cases of unexplained pancytopenia. Moreover, in our population megaloblastic anemia is a common entity resulting into pancytopenia, so it must be timely diagnosed in order to avoid serious hematological and neurological consequences.